Comparison of speech articulation and intelligibility in palatally contoured dentures using a novel rugae duplication technique: A clinical study - Vaswani, Priya; Sanyal, Pronob; Prajapati, Ankur (Journal of Oral and Dental Sciences, 2015)
Background: Speech is essential to human activity. Loss of teeth is usually accompanied by eventual loss of oral morphology responsible for articulation. Palatal rugae contour has an important role in phonetics by production of linguo-palatal sounds that involves the contact between tongue and palate. Objectives: To analyze the improvement in linguo-palatal sounds by duplicating the existing rugae in maxillary complete denture prosthesis using two different impression materials in shallow, medium & deep palatal vault configuration. Methods: Twenty four completely edentulous patients were selected that were categorized eight in each category of shallow, medium & deep palatal vaults. Existing rugae were duplicated using mucocompressive and mucostatic impression material, wax pattern obtained through these impressions were incorporated in maxillary dental prosthesis. Later speech was recorded and analyzed by a speech pathologist with an aid of speech rating scale over a period of eight weeks. Results: Mann-Whitney U test and Wilcoxon matched pair test showed statistical significance in speech improvement (p<0.05) when mucostatic impression derived rugae pattern was incorporated in upper arch prosthesis. Conclusion: Using the presently described rugae duplication technique, speech improvement is rapid in case when mucostatic impression material was used.